Estudio de prefactibilidad del montaje de una empresa de consultoría para proyectos de uso de energías renovables en el sector industrial de Colombia (2016)
Prefeasibility level studies and financial evaluation for a selected alternative for setting up consultancy enterprise to projects using renewable energies (from sun and wind) to big and medium companies of industrial sector in Colombia.